Training in transition : comparative analysis and proposals for the modernization of vocational education and training in Poland - Adamski, Wladyslaw [Verfasser]; Baethge, Martin [Verfasser]; Bertrand, Oliver [Verfasser]; Jozefowicz, Adam [Verfasser]; Grootings, Peter [Herausgeber] (Office for Official Publications of the European Communities, 1993)
"The report begins with an overview of the past and future of Polish vocational education and training (VET) in terms of constraints and challenges offered by developments in Polish society. It then analyses three environmental aspects of future VET: labour market developments, status of education in society and demographic trends. In contrast the report summarises the major challenges and trends facing VET in Western societies, and while emphasizing the need for an internationally motivated solution to Polish reform, it stresses that there are no models that can simply be copied. Developments and experiences in Western Europe are compared to basic characteristics of Polish VET, with analysis concentrating on: structure and location of VET; contents and curricula; monitoring and evalution; resources; adult and continuing education. The final chapter looks at how to change many things at once in a situation where the future is uncertain and resources are lacking." (Editor, BIBB-Doku)
Keywords: I 2.2.2 Osteuropa; I 2.2 Europa; Polen; Berufsbildungssystem; Internationaler Vergleich; Europa; Zukunftsperspektive